The Influence of Health Education Through TikTok Media on Adolescents' Knowledge and Attitudes about Premarital Sex - Liawati, Liawati; Nuraeni, Rika Mahardika (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Premarital sexual conduct in teenagers is a matter of reproductive health that may lead to an increased chance of unintended pregnancies, sexually transmitted diseases, and dropping out of school. Social media platforms, especially TikTok, could serve as a powerful tool for education, as they align well with the traits of adolescents. This research seeks to evaluate how effective TikTok education is in influencing knowledge and attitudes regarding premarital sex among female pupils from SMA Negeri 1 Rengasdengklok. The approach taken for this investigation was a pre-experimental design involving a one-group pretest–posttest. The participant group included 85 female students from grade XI IPA, chosen through proportionate stratified random sampling. Information was collected via a validated and reliable questionnaire, subsequently analyzed with the Wilcoxon Signed-Rank Test. Prior to the educational intervention, 95.3% of participants displayed poor knowledge while 84.7% exhibited negative attitudes. Following the TikTok education, all participants (100%) demonstrated good knowledge and positive attitudes. The analysis revealed a notable difference between the pretest and posttest results concerning both knowledge and attitude (p < 0.001). Health education utilizing TikTok proves effective in enhancing knowledge and developing favorable attitudes towards premarital sexual behavior. This approach could represent an innovative option for advancing reproductive health education that resonates with young people's traits.